2019
DOI: 10.1038/s41467-019-11349-9
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-scale engineering of indium oxide promotion by palladium for methanol production via CO2 hydrogenation

Abstract: Metal promotion is broadly applied to enhance the performance of heterogeneous catalysts to fulfill industrial requirements. Still, generating and quantifying the effect of the promoter speciation that exclusively introduces desired properties and ensures proximity to or accommodation within the active site and durability upon reaction is very challenging. Recently, In 2 O 3 was discovered as a highly selective and stable catalyst for green methanol production from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
347
4
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 319 publications
(406 citation statements)
references
References 57 publications
21
347
4
10
Order By: Relevance
“…Moreover, the formation of Pt dimers and trimers can also be excluded due to the high dimerization and trimerization energy of 2.15 eV Pt −1 and 2.61 eV Pt −1 , respectively ( Supplementary Fig. 1) 16,27 . Therefore, we expect the anchored Pt single atom enable to withstand hightemperature conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the formation of Pt dimers and trimers can also be excluded due to the high dimerization and trimerization energy of 2.15 eV Pt −1 and 2.61 eV Pt −1 , respectively ( Supplementary Fig. 1) 16,27 . Therefore, we expect the anchored Pt single atom enable to withstand hightemperature conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The choice of support is vital for the successful synthesis of SACs, which determines both their thermal stability and durability. Several techniques and different supports have been reported for the preparation of SACs [12][13][14][15][16] . For example, Zhang and colleagues prepared Pt/FeO x SACs via the substitution of surface Fe atoms by Pt in the crystal lattice of FeO x 7,17 .…”
mentioning
confidence: 99%
“…Consequently, high space time yields (STYs) of 0.405 and 0.125 mmol g − 1 h − 1 were achieved for AA and PA, respectively (Supplementary Table 1). Although numerous reports have been published on the direct hydrogenation of CO 2 to methanol 5,[42][43][44][45] , C 5+ liquid hydrocarbons [46][47][48][49][50] , and aromatics 19,20,[51][52][53] , studies dedicated to the direct CO 2 conversion to monocarboxylic acids have been extremely rare. A single article, which described the possibility of forming AA over a Ag-promoted Rh/SiO 2 catalyst, was published in the early 1990s 34 ; however, the reported production rate of AA was very low (~ 0.035 mmol g − 1 h − 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The highest methanol selectivity (61%) was obtained at an In/Pd ratio of 2:1, whereas In 2 O 3 / SiO 2 only had a methanol selectivity of 24%. Frei et al (2019) showed that the size and location of Pd species influence the performance of Pd-promoted In 2 O 3 , and their findings are illustrated in Fig. 2.…”
Section: Indium-based Catalystsmentioning
confidence: 91%
“…More recently, In-based catalysts have gained much research interest due to its high methanol selectivity over a wide range of temperatures. Promoters can further enhance the methanol synthesis rate of In-based catalysts, which is significantly affected by the atomicscale architecture (Frei et al 2019).…”
Section: Introductionmentioning
confidence: 99%